Chemical Embryology Redux: Metabolic Control of Development. Issue 8 (August 2020) - Song, Yonghyun; Shvartsman, Stanislav Y.
Abstract : New studies of metabolic reactions and networks in embryos are making important additions to regulatory models of development, so far dominated by genes and signals. Metabolic control of development is not a new idea and can be traced back to Joseph Needham's 'Chemical Embryology', published in the 1930s. Even though Needham's ideas fell by the wayside with the advent of genetic studies of embryogenesis, they demonstrated that embryos provide convenient models for addressing fundamental questions in biochemistry and are now experiencing a comeback, enabled by the powerful merger of detailed mechanistic studies and systems-level techniques. Here we review recent results from studies that quantified the energy budget of embryogenesis in Drosophila and started to untangle the intricate connections between core anabolic processes and developmental transitions. Dynamic coordination of metabolic, genetic, and signaling networks appears to be essential for seamless progression of development. Highlights: Dynamic coordination of metabolic, genetic, and signaling networks appears to be essential for seamless progression of development. Throughout fly embryogenesis, the energy production rate increases linearly in time until hatching, summing up to a total of ~10 mJ. Fly embryos synthesize deoxynucleoside-triphosphates (dNTPs) 'on the go' while undergoing the nuclear cleavage cycles, during which the dNTP concentration is maintained through a negative feedback mechanism. Without negative feedback, uncontrolled dNTP production leads to the failure of the deceleration of the nuclear cleavage cycles during the midblastula transition, insufficient gene expression, and embryonic lethality.